A Historical Reflection of the Colada Morada, a Traditional Ecuadorian Drink - Albán Barreiro, Manuela (2023)
Through archival research, this article provides a historical account of the traditional Ecuadorian beverage, colada morada. In this sense, we start from its pre-Columbian roots, and we also analyze global processes that might have shaped its production and consumption. In addition, we reflect on colada morada today: how it is consumed within the Catholic practice of the Day of the Dead (on November 2nd) with differentiated characteristics between urban and rural areas, its fixation as an element of Ecuadorian national identity both to Ecuadorians residing in the country and to those who have migrated, and its current role as part of Ecuadorian national cultural/ food heritage.